KPC-producing Klebsiella pneumoniae bloodstream isolates from Brazilian hospitals: What (still) remains active?. (December 2018) - Antochevis, Laura C.; Magagnin, Cibele M.; Nunes, Aline G.; Goulart, Taíse M.; Martins, Amanda S.; Cayô, Rodrigo; Gales, Ana C.; Barth, Afonso L.; Zavascki, Alexandre P.
Highlights: Few therapeutic options remain active against polymyxin-resistant KPC-producing Klebsiella pneumoniae (KPC-Kp). Resistance to polymyxin B (PMB) and other antimicrobials using different breakpoints was evaluated. High rates of PMB resistance (25.3%) were found among 158 KPC-Kp isolates. Eighteen clones were found in PMB-resistant isolates, mostly belonging to CC11. Abstract: Objectives: This study assessed susceptibility to polymyxin B (PMB) and alternative antimicrobials, with focus on aminoglycosides and tigecycline, according to different breakpoints in KPC-producing Klebsiella pneumoniae (KPC-Kp) bloodstream isolates from Brazilian hospitals. Methods: Bloodstream K. pneumoniae isolates non-susceptible to any of the three carbapenems (meropenem, imipenem or ertapenem) from four Brazilian tertiary-care hospitals were selected. Antimicrobial susceptibility was determined and interpreted according to distinct breakpoints. Twenty-nine PMB-resistant KPC-Kp isolates were selected for molecular typing. Results: A total of 158 KPC-Kp were analysed. MIC50/90 values for PMB were 0.25/16 mg/L; 40 isolates (25.3%) were resistant to PMB. MIC50/90 values for meropenem were 32/ ≥ 256 mg/L; no isolates were susceptible to meropenem according to CLSI, but 10 isolates were intermediate using EUCAST breakpoints (1, MIC = 4 mg/L; 9, MIC = 8 mg/L). MIC50/90 values for tigecycline were 2/8 mg/L; 53 (33.5%) and 94 (59.5%) isolates were susceptible according to EUCAST and FDA breakpoints, respectively. MIC50/90 values were 32/ ≥ 64 mg/L for amikacin and ≥16/ ≥ 16 mg/L for gentamicin; 48 (30.4%), 28 (17.7%) and 16 (10.1%) were susceptible to amikacin according to CLSI, EUCAST and USCAST, respectively, but susceptibility rates to gentamicin were <7.0%. Eighteen distinct clonal profiles were identified among 29 PMB-resistant isolates by DNA macrorestriction. Most clones belonged to CC11. Conclusion: Elevated rates of PMB-resistant KPC-Kp bloodstream infections were found in four Brazilian hospitals, mostly of polyclonal origin. Alternative antimicrobials with the highest in vitro activity were tigecycline and amikacin, although susceptibility rates significantly decreased using criteria with stricter breakpoints (e.g. EUCAST, USCAST).